Enhanced gelling properties and hydration capacity of ginkgo seed proteins by genipin cross-linking. (15th January 2023) - He, Zhendong; Liu, Changqi; Zhao, Jing; Guo, Fengxian; Wang, Yaosong
Highlights: Ginkgo seed protein isolate (GSPI) hydrogel was fabricated by heat-induced gelation. Satisfactory cross-linking was achieved by genipin. Genipin cross-linking promoted the aggregation of proteins and enhanced the gelling properties thereof. Genipin cross-linking improved water holding capacity of the GSPI gels. Abstract: The present study investigated the effects of genipin cross-linking on the gelling properties of ginkgo seed protein isolate (GSPI). Cross-linking of GSPI was achieved with different concentrations (0, 0.05, 0.1, 0.2, 0.4, 0.6% w/v) of genipin at pH 6.0. Compared to pure GSPI, genipin treatment led to lower solubility, surface hydrophobicity, and fluorescence intensity, while promoted protein aggregation. Cross-linked GSPI gels exhibited markedly improved gelling properties and water holding capacity (WHC), with up to 2.1-fold increases in gel hardness and 1.3-fold increases in WHC over non-treated GSPI gel. Electrophoresis and Fourier-transform infrared spectroscopy confirmed the cross-linking. Moreover, microstructural examination showed that cross-linking with genipin resulted in protein aggregation and more porous gel matrix. Overall, genipin cross-linking demonstrated great potential for the enhancement of gelling properties of ginkgo seed protein. The current research may expand the utilization of ginkgo seeds in food applications.